SMALL STATE'S CAPTURED SUSTAINABLE DEVELOPMENT AS A CONSEQUENCE OF INSTITUTIONAL WEAKNESS AND POLITICAL POPULISM: WESTERN BALKANS CASE STUDY (UKLO Proceedings, 2026)
Introduction: The purpose of this paper is to analyze to role of institutional and political frameworks, as a variable in the ongoing process of securing sustainable development. Authors thesis would rely on the explanation that the sustainable development is directly conditioned of the political and institutional frameworks in the case of small states with extremely limited political, economic, military and natural resources. Thus, the research question would be: What are the available instruments to small states in the process of securing development and sustainability?Methods: In the methodological context the topic was chosen based on its topicality and because it contributes to the raising the discussion about the role of small states in the chapter of international relations where the sustainable development agenda is almost at the top. The goal is also to acquire new scientific knowledge, particularly in the context of determining the room for maneuver of small states in their foreign policy actions in the context of contributors to the already mentioned agenda. The authors will use basic analytical methods, such as content analysis of literature and documents and abstraction, to highlight the important characteristics that determine the foreign policy actions of small. Among analytical methods, specialization will also be used to pay special attention to the correlation between the sustainable development agenda and the foreign policy behavior of small states. When it comes to synthetic basic methods, concretization will be used to analyze the empirical example of the Western Balkans. On the other hand, induction will be applied in the conclusion section to establish a broader contemporary understanding about the small states in contemporary international relations based on the empirical example.Results: Based on the available data, results and effectiveness of foreign policy activities, including internal political and institutional flows within the states of the so-called Western Balkans region used as an empirical example, results will provide explanation why the sustainable development agenda is "captured" from the perspective of their institutional and political dysfunctionality.Discussion: From the theoretical perspective, authors will use the understanding of institutionalism in order to confront it to neoclassical thesis about the individual role in the decision-making process, that is quite important for understanding internal flows of small states, as well as foreign policy positioning, bearing in mind the fact that sustainable development represents a process composed of internal policies and foreign policy activism.